1999
DOI: 10.1097/00001756-199902250-00023
|View full text |Cite
|
Sign up to set email alerts
|

Expression of mRNA encoding α1E and α1G subunit in the brain of a rat model of absence epilepsy

Abstract: Low voltage-activated calcium channels are thought to play a key role in the generation of spike and waves discharges characteristic of absence epilepsy. Therefore, the expression level of mRNA encoding calcium channel alpha1E and alpha1G subunits was measured in the brain of genetic absence epilepsy rats from Strasbourg (GAERS). Using quantitative RT-PCR and in situ hybridization, no difference was found in alpha1G mRNA expression between GAERS and control animals, while a decreased expression of alpha1E was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…The expression of messenger RNA encoding the calcium channel ␣1E subunit was recently reported to be decreased in the brain of genetic absence epilepsy rats from Strasbourg (GAERS). 34 This protein, which is a good can-didate because of its function and its brain-specific expression, reinforces the potential importance of the 1q25-q31 locus.…”
Section: Genetic Studymentioning
confidence: 61%
“…The expression of messenger RNA encoding the calcium channel ␣1E subunit was recently reported to be decreased in the brain of genetic absence epilepsy rats from Strasbourg (GAERS). 34 This protein, which is a good can-didate because of its function and its brain-specific expression, reinforces the potential importance of the 1q25-q31 locus.…”
Section: Genetic Studymentioning
confidence: 61%
“…Gabaergic interneurons of the reticular thalamic nucleus and cortex as well as extrathalamocortical structures were clearly shown to express Ca v 2.3 (Soong et al, 1993;De Borman et al, 1999;Talley et al, 2000;van de Bovenkamp-Janssen et al, 2004;Weiergra¨ber et al, 2006). Most studies on the role of Ca v 2.3 in absence epileptogenesis were carried out on the Genetic Absence Epilepsy Rats from Strasbourg (GAERS) and the Wistar Albino Glaxo rats (WAG/Rij).…”
Section: Ca V 23 In Non-convulsive Seizures-functional Interdependenmentioning
confidence: 99%
“…Experimental studies of genetic rat models of absence epilepsy have indicated that the perioral region of the somatosensory (parietal) cortex initiates the seizure activity that entrains the thalamo-cortical circuit and produces generalized SWD activity (Meeren et al, 2002;Polack et al, 2007). No structural changes were observed in SWD generator brain regions, but several changes at the subcellular level have been observed, such as changes in receptor subunits (Beyer et al, 2008;van de Bovenkamp-Janssen et al, 2006) and ion channel expression (de Borman et al, 1999;Klein et al, 2004;Kole et al, 2007;Lakaye et al, 2002;van de Bovenkamp-Janssen et al, 2004;Weiergräber et al, 2008). Recently, a proteomics study identified ATP synthase subunit delta, 14-3-3 zeta isoform, myelin basic protein and macrophage migration inhibitory factor as differentially expressed proteins in these regions in Genetic Absence Epilepsy Rats from Strasbourg (GAERS) (Danis et al, 2011).…”
Section: Discussionmentioning
confidence: 99%